Toxoplasma gondii in sheep: Serological occurrence at slaughterhouse level in Italy and environmental risk factors - Condoleo, Roberto; Rombolà, Pasquale; Palumbo, Roberta; Santori, Davide; Serra, Salvatore; Tonon, Sara; Bosco, Antonio; Sezzi, Erminia (Frontiers in Veterinary Science, 2023)
Toxoplasmosis is a parasitic disease affecting a wide range of species, including humans, and can be responsible for important clinical manifestations such as abortion and neurological signs. Sheep show a remarkable susceptibility to its causative agent, Toxoplasma gondii, and zoonotic transmission may occur in case of consumption of undercooked meat obtained from infected animals. Toxoplasma gondii seroprevalence in sheep can significantly vary on a geographical basis, as shown by numerous surveys conducted worldwide. To investigate environmental and climate conditions that may affect the likelihood of ovine infection, 405 serum samples from selected sheep raised in 91 farms were collected from two abattoirs, with each abattoir receiving animals from two regions (1/Tuscany-Latium and 2/Campania-Basilicata). The seroprevalence of infection in all examined animals was 53.8%. Young animals (n = 165) had a lower likelihood of being T. gondii positive compared to the adults (OR = 0.21), and the seropositive rate of animals slaughtered in abattoir 2 was significantly higher than that of animals slaughtered in abattoir 1 (60.5 vs. 43.2%, p < 0.01). The significant bioclimatic variables (p < 0.05) associated with the presence of T. gondii antibodies were related to areas with a lower range of temperature and higher precipitation. In conclusion, this study expands on the interpretation of serological data, with the inclusion of environmental and climatic variables, as possible risk factors in the spread of toxoplasmosis in the study area. These findings provide novel insights to support public health measures, such as risk-based control plan, and contribute to a “One Health” approach, taking into account the environmental and climatic perspectives.